Analysis of Interfaith Marriage from the Perspective of Maqashid Shariah AS-Syathibi - Sebayang, Muhammad Alfalah; Tanjung, Dhiauddin (Judge : Jurnal Hukum, 2024)
Interfaith marriages are in the news on TV and social media, with both pros and cons. Those who are pro argue that such actions are based on humanity and human rights and do not care about religious differences as long as the family is harmonious and happy. On the other hand, the cons argue from the perspective of positive law, which prohibits it in Indonesia, and according to fiqh, the marriage is invalid. The purpose of this study is to understand how Maqashid al-Syariah Syatibhi views interfaith marriage and what its impact is. The method used is descriptive-analytical, examining Indonesian normative or positive law, conceptually comparing it with the Compilation of Islamic Law (KHI), and investigating arising issues. The results of this study indicate that interfaith marriage has more adverse effects than benefits. The data collection technique uses a comparative analysis of interfaith marriage and Maqasid Sharia. The results of this study indicate that interfaith marriage is not allowed in Islam because it contradicts five maqasid sharia concepts: (1) Maintaining Religion, suggesting religion as a life guide; (2) preserving the soul, as different teachings may cause internal conflict; (3) preserving the mind, as one might be led astray by improper use of reason; (4) preserving offspring, as different religions could hinder the fulfillment of their duties as Allah’s caliphs; (5) maintenance of property, as different religions prevent mutual inheritance. Marriages meant to foster household harmony often end in divorce due to disputes over children’s religious choices and inheritance issues. The conclusion of this research is that interfaith marriage is prohibited by Indonesian positive law and haram according to fiqh. Meanwhile, Maqashid al Sharia views the number of evils as outweighing the good.